PSIKOEDUKASI BODY IMAGE POSITIF SEBAGAI STRATEGI PENCEGAHAN GANGGUAN MENTAL PADA GENERASI Z - Ria Safaria Sadif; Maria Ulfa; Melda Widya Rosady (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community engagement activity aims to enhance Generation Z’s understanding and skills in developing a positive body image as a means of preventing mental health issues. The method employed is participatory psychoeducation, which integrates education, discussion, self-reflection and skills training. The activity was carried out in Mantowu Village, Buton Regency, with 15 participants from the Generation Z youth category. The results of the activity showed that participants gained an understanding of body diversity and realized that beauty standarts are relative. Participants were also able to think more critically about digital content depicting the ideal body. Furthermore, participants demonstrated an initial ability to manage negative emotions arising from social comparison and were able to accept themselves through reflection exercises and positive affirmations. Overall, this activity succeeded in improving mental health literacy and fostering a positive body image among adolescents.